Perspectives on political party death: theorizing and testing Downsian and sociological rationales. Issue 1 (16th November 2018) - Bolleyer, Nicole; Ibenskas, Raimondas; Bischoff, Carina
Abstract: Which of the new political parties that emerged in advanced democracies faded away and which ones managed to survive and why? Considering a party as dead once it ceases to nominate candidates in any elections, we develop two sets of hypotheses to account for party death derived from two conceptions of political parties. One conceptualizes parties as vehicles formed by career-oriented politicians eager to maximize individual rewards. Failure to deliver seats or government access is therefore expected to predict an earlier death. The other conceptualizes parties as societal organizations that serve representational functions valued in themselves by elites and members alike. This conception stresses the importance of roots in society or ideological novelty. Using survival analysis, we test our hypotheses in 17 advanced democracies based on a new data set covering 144 new parties from birth until their (potential) death. Arguments derived from both conceptions have significant support stressing the complexity of the drivers underpinning parties' very existence.